Fuzzy solution in fuzzy linear programming problems - Tanaka, Hideo; Asai, Kiyoji (IEEE transactions on systems, man, and cybernetics, 1984)
Conventional mathematical programming problems are to maximize an objective function subject to constraints. In the real decision problems, however, a satisfaction criterion might be more useful than a criterion of maximizing an objective function in making the decision under fuzzy constraints. From this point, fuzzy linear programming problems are discussed in which both constraints and objective functions are assumed to be of fuzzy inequalities. The problem is to obtain a fuzzy solution such that the fuzzy inequalities hold. In a fuzzy solution the greatest possibility distribution of decision is determined. Our aim is to find out how fuzzy solution will be possible. This problem can be reduced to the conventional linear programming problem so that this fuzzy linear programming problem can be easily solved by the ordinary algorithms of linear programming.